Padang as a significant urban element of Kuala Lumpur City - Harun, Nor Zalina (IIUM Press, 2015)
After almost 130 years, Dataran Merdeka has witnessed many events and changes. Today, the area of padang diminished allowing space for the construction of several buildings and a road. Occasionally it continued to be the centre of administrative district. However, the most dramatic changes occurred in the mid 1980’s where it was completely dug up to accommodate underground car park and commercial centres comprised of restaurants and business outlets known as Putra Plaza. It was then roofed over and turned with many other landscape features on its top such as a stage show, and gazebo, and pedestrian walkways built around it. The underground plaza had, however, stopped operating after a big flood hit Kuala Lumpur in 2003 (Pertubuhan Arkitek Malaysia, 2007). Now the padang is used as a marking point to indicate the distance from any places in Malaysia to Kuala Lumpur city centre (Amree, 2007). It has become even more easily spotted since the reputedly the world’s tallest flagpole was placed at the edge of its lawn. Today, the padang is still the place for meeting, recreational and festivities. Parades and special ceremonies such as independence celebration and private and public gatherings have continuously taken place on it. The flexible use of the padang for important civic functions also has, in particular, led to the utilization of adjacent roads as part of the open space as a parade ground (Federal Department of Town and Country Planning, 2005). In short, padang was a centre of social life and a place to promenade where the people communicate and unite.